Pengaruh Keputusan Investasi Dan Leverage Terhadap Kinerja Keuangan Perusahaan Tekstil Dan Garmen Yang Terdaftar Di Bursa Efek Indonesia Tahun 2020-2024 - Ameliya Delma Sari; Indrayeni . (Jurnal Akuntansi Keuangan dan Bisnis, 2026)
This study aims to analyze the effect of investment decisions and leverage on the financial performance of textile and garment companies listed on the Indonesia Stock Exchange (IDX) for the 2020-2024 period. Using a causal associative quantitative method, the sample includes 15 companies with 64 observations after outlier elimination. Secondary data from annual reports were analyzed using multiple linear regression via SPSS software. The partial test results indicate that investment decisions have no significant effect on financial performance (Sig. 0.173 > 0.05), while leverage significantly impacts performance (Sig. < 0.05). The Adjusted R-Square value of 0.192 suggests that both independent variables explain 19.2% of the variation in financial performance (ROA). The study concludes that funding policies through leverage play a crucial role in determining profitability in this capital-intensive industry, whereas investment decisions proxied by PER do not directly influence current earnings. Companies are advised to optimize their capital structure to maintain financial stability post-pandemic.